ICNP® nursing diagnostics for people in-home care - Ingryd Nathany Mendes Sousa; Daniel Vinícius Alves Silva; Júlia Rocha do Carmo; Joanilva Ribeiro Lopes; Nuno Damácio de Carvalho Félix; Fabíola Afonso Fagundes Pereira; Diego Dias de Araújo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to identify ICNP® nursing diagnoses in people attended in a home care program. Methods: cross-sectional study with 131 patients of Home Health Care in a northern municipality of Minas Gerais, Brazil, applied a questionnaire based on Basic Human Needs. It was performed the identification and validation by consensus of specialists with support in Risner's diagnostic reasoning, of the nursing diagnoses of ICNP®, version 2019. Results: from 77 nursing diagnoses, most are inserted in the psychobiological needs (n = 66) and refer to the domains Nutrition; Hydration and electrolytic regulation; Cutaneous-mucous integrity; Locomotion, body mechanics and mobility; Body care; and Learning, Sociability, Recreation, and leisure. From total, forty are negative, followed by positive formulations (n = 15), clinical findings (n = 15) and risk (n = 7). Conclusions: a profile of the nursing phenomena common to home care is presented, which can be used by nurses in clinical practice, teaching, research, and management.